In Situ Synthesis Mechanism and Photocatalytic Performance of Cyano-Bridged Cu (I)/Cu (II) Ultrathin Nanosheets - Li, Shixiong; Qiang, Jiawei; Lu, Lifei; Yang, Shaolong; Chen, Yufeng; Liao, Beiling (Frontiers in Chemistry, 2022)
In situ synthesis of cyano-bridged Cu (I)/Cu (II) complexes usually requires organometallic catalysts or is carried out under high-temperature and high-pressure conditions. Herein, the cyano-bridged two-dimensional Cu (I)/Cu (II) photocatalyst, [Cu2 (Py)3(CN)3]n (1), is synthesized in situ at room temperature. The in situ synthesis mechanism of 1 shows that the partial Cu (II) complex catalyzed the C-C bond cleavage of 1,3-isophthalonitrile (L) to introduce -CN and generate Cu (I)/Cu (II). Its ultrathin nanosheets can be obtained by adding sodium dodecyl benzene sulfonate and performing ultrasonic synthesis in the process of synthesis 1. The ultrathin nanosheets of 1 have a lattice distance of about 0.31 nm, and it can rapidly decompose methylene blue (MB) (K = 0.25 mg L−1 min−1 at pH = 3). This research work is beneficial for in situ synthesis of cyano-bridged Cu (I)/Cu (II) complexes at room temperature and explores their synthesis and photocatalytic mechanism.